Civic Education and Competences for Engaging Citizens in Democracies - Print, Murray.; Lange, Dirk. (Civic And Political Education ;, 2013)
Civic Education and Competences for Engaging Citizens in Democracies Murray Print University of Sydney and Dirk Lange Leibniz University of Hannover What competences do young citizens need to be considered as active and engaged in the context of a modern Europe? In 2011 an invited research symposium of leading civic and political educators, social scientists and educational administrators from Europe met in Hannover, Germany to consider this key concern facing Europe today. In examining the above question the symposium addressed two significant issues: 1. Identify key competencies required for active citizenship of young people in Europe of the future. 2. Translate those competencies to school-based activities in the form of curricular and pedagogical strategies. The group addressed these questions through discussion in the symposium and through previously prepared papers. Subsequently the group participated in a modified Delphi Technique to identify the key competences and the final competences are presented in this book. The chapters of this book represent the contribution of the participants before, during and after the symposium with opportunities for review and reflection. Murray Print and Dirk Lange are professors from the University of Sydney and Leibniz University of Hannover respectively and are national leaders in civics and citizenship education in their respective countries. They have brought together a group of leading European civic and citizenship educators from different academic fields to explore the key issue and to identify the competences for young people to become active and engaged European citizens.